Genetic changes during leukemic transformation to secondary acute myeloid leukemia from myeloproliferative neoplasms. (July 2022) - Kim, TaeHyung; Ahn, Jae-Sook; Son, Meong Hi; Novitzky-Basso, Igor; Yi, Seong Yoon; Ahn, Seo-Yeon; Jung, Sung-Hoon; Yang, Deok-Hwan; Lee, Je-Jung; Choi, Seung Hyun; Lee, Ja-yeon; Moon, Joon Ho; et al.
Abstract: Leukemic transformation (LT) is the main cause of death for patients with myeloproliferative neoplasms (MPNs). To study genetic changes associated with the LT, we performed targeted sequencing in 26 MPN patients including 21 with paired samples. We observed that, besides three driver genes, IDH2 (19%) and ASXL1 (14%) were also frequently mutated at MPN diagnosis. Although variant allele frequencies (VAFs) of mutations in DNA methylation and spliceosome did not expand during LT, they were enriched in patients with LT (the LT group). At follow-up, we also observed acquisition of mutations, mostly in the LT group. When considering dynamics of VAF from diagnosis to follow-up, VAFs in the LT group expanded (median VAF, 36.7–43.7%, p = 0.045). In contrast, mutations in patients with no clinical progression was stable (median VAF, 36.3–35.7%, p = 0.739). Overall, the present study demonstrates genetic changes during LT and provides the potential for prognostic application. Highlights: Mutations in DNA methylation/spliceosome genes are enriched in the LT group. Newly detected mutations are common during leukemic transformation. Allelic burdens of pre-existing mutations increase during leukemic transformation.